FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN HIPERTENSI PADA LANSIA DI POSYANDU LANSIA DI WILAYAH KERJA PUSKESMAS PB SELAYANG II KECAMATAN MEDAN SELAYANG - Hazellarissa Valda Asari; Rasmaliah .; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Hypertension is a silent killer causing an iceberg phenomenon. The prevalence of hypertension increased with increasing age.Health Research Association (Riskesdas) in 2013 showed the prevalence of hypertension in Indonesia reached 25,8%. While in North Sumatera, from 10 non-communicable diseases it is known that hypertension prevalence is the second highest with 9,4% prevalence after joint disease which has 11,9% ( Riskesdas in a Number of Province North Sumatra 2013). To determine factors associated with elderly hypertension in Elderly Integrated Service Post at the Work Area of Public Health Center PB Selayang II conducted an analytic survey research by using cross sectional approach. The population is all elderly who live in Integrated Service Post at the Work Area of Public Health Center PB Selayang II. The sample is elderly who visit 9 Elderly Integrated Service in amounting to 112 people. The data collected is primary data from direct interview with respondents using questionnaire. The data analysis done by univariate and bivariate (Chi-square test). Based on the results of the research shown that point prevalence rate of hypertension was 45,5%, the highest proportion of hypertension of the respondents at the category ages of ≥60 years old (51,9%), male gender (50%), family history (63,2%), nutritional status (67,4%), inadequate physical activity (55,8%),medium to heavy smoking status (58,30%),smoking by male (53,3%) and smoking by female (42,9%). The results of bivariate analysis shown that 3 variables had a significant association with the elderly hypertension, i.e. history of family (p=0,007 RP=1,731), nutritional status (p=0,000; RP=2,115), and physical activities (p=0,028; RP=1,613). For elderly who has a family history of hypertension should do regular blood test and elderly with obesity and irregular physical activity should maintain ideal body weight and perform regular physical activity. For elderly Integrated Service Post officers, it is necessary to increase the role in guiding the elderly for routine examination of risk factors of hypertension in the elderly, so that the elderly can prevent these risk factors. Keywords: Hypertension, Elderly, Elderly Integrated Service Post